A proposed system for the application of total quality management in the institutes of science and technology of physical and sports activities in Algeria. - طراد, توفيق; قرصان , عبد الحق (sports creativity, 2025)
The study aimed to propose a system for the application of total quality management in the institutes of science and technology of physical and sports activities in Algeria, by following the descriptive analytical approach, this study touched on the concept of total quality management in higher education and the reality and obstacles to its application in istaps, and we conclude the axes of the proposed themes for the implementation of total quality management in these institutes in the light of the recommendations of pioneers and experts, as well as previous experiences and studies in the field of total quality management in higher education, finally, the researcher recommends the need to work on the application of total quality management in the istaps in Algeria, in order to achieve continuous improvement of the pedagogical process, focus on the beneficiary, and support the administrative leadership of this administrative orientation and create a good organizational culture based on respect and cooperation.